방문건강관리사업 대상 노인의 구강건강 관련 삶의 질과 관련 요인 - 이근유; Keun Yoo Lee; 조영식; Young Sik Cho; 임순연; Soon Ryun Lim (Chiwisaeng gwahakoeji, 2015)
The aim of this study was to investigate the relationship between the oral health status of elderly under visiting health care and their oral health-related quality of life. The subjects were 300 elderly under visiting health care program over 65 years old in Asan city and they were interviewed. The result showed that average Geriatric Oral Health Assessment Index (GOHAI) score was 37.36 and the lowest scored question was ``never satisfied with the oral condition``. In GOHAI related to oral health behaviors, unmet dental treatment experience was statistically significant (p＜0.001). In overall GOHAI, number of remaining teeth (p＜0.001) and the age had statistical significance and men had higher score in pain and discomfort (p＜0.05), under age of 74 limited function factors score was high (p＜0.01). The number of remaining teeth had statistical significances in most factors except pain and discomfort (p＜0.001). The factors affecting GOHAI were age (p＜0.05), number of remaining teeth (p＜0.001) and perceived health state (p＜0.001). In order to improve oral health-related quality of life of elderly receiving visiting oral health care services, it is necessary to increase denture support by securing budgets and developing oral health promotion programs at the local government level.